Sprint running performance and technique changes in athletes during periodized training: An elite training group case study - Bezodis, I. N.; Kerwin, D. G.; Cooper, S.-M.; Salo, A. I. T. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To understand how training periodization influences sprint performance and key step characteristics over an extended training period in an elite sprint training group. Methods: Four sprinters were studied during 5 mo of training. Step velocities, step lengths, and step frequencies were measured from video of the maximum velocity phase of training sprints. Bootstrapped mean values were calculated for each athlete for each session, and 139 within-athlete, between-sessions comparisons were made with a repeated-measures analysis of variance. Results: As training progressed, a link in the changes in velocity and step frequency was maintained. There were 71 between-sessions comparisons with a change in step velocity yielding at least a large effect size (>1.2), of which 73% had a correspondingly large change in step frequency in the same direction. Within-athlete mean session step length remained relatively constant throughout. Reductions in step velocity and frequency occurred during training phases of high-volume lifting and running, with subsequent increases in step velocity and frequency happening during phases of low-volume lifting and high-intensity sprint work. Conclusions: The importance of step frequency over step length to the changes in performance within a training year was clearly evident for the sprinters studied. Understanding the magnitudes and timings of these changes in relation to the training program is important for coaches and athletes. The underpinning neuromuscular mechanisms require further investigation but are likely explained by an increase in force-producing capability followed by an increase in the ability to produce that force rapidly.